2021
DOI: 10.3390/molecules26051225
|View full text |Cite
|
Sign up to set email alerts
|

Phage-Display Based Discovery and Characterization of Peptide Ligands against WDR5

Abstract: WD40 is a ubiquitous domain presented in at least 361 human proteins and acts as scaffold to form protein complexes. Among them, WDR5 protein is an important mediator in several protein complexes to exert its functions in histone modification and chromatin remodeling. Therefore, it was considered as a promising epigenetic target involving in anti-cancer drug development. In view of the protein–protein interaction nature of WDR5, we initialized a campaign to discover new peptide-mimic inhibitors of WDR5. In cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The Ph.D.™-C7C phage library of random cyclic peptides with a disulfide constrained loop was applied in the WBM-targeting biopanning. As we disclosed previously, 23 peptides with arginine can easily bind to the WIN site of WDR5. So, a small molecular inhibitor ( WIN-IN-4 ; CAS: 2407457-36-5) with sub-nanomole binding activity was employed to block the WIN site before selection.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The Ph.D.™-C7C phage library of random cyclic peptides with a disulfide constrained loop was applied in the WBM-targeting biopanning. As we disclosed previously, 23 peptides with arginine can easily bind to the WIN site of WDR5. So, a small molecular inhibitor ( WIN-IN-4 ; CAS: 2407457-36-5) with sub-nanomole binding activity was employed to block the WIN site before selection.…”
Section: Resultsmentioning
confidence: 56%
“…The WDR5 (residues 23–483) expression strain with His 6 -sumo tag at N-terminal was preserved in-house. 23 The 500 mL terrific broth cultures supplemented with 50 μg mL −1 kanamycin were inoculated with 1/100 saturated E. coli bacterial culture for overnight growth at 37 °C until the OD 600 reached 0.8. The protein was induced at 0.5 mM isopropyl β- d -1-thiogalactopyranoside (IPTG) and cultured at 18 °C for 16 h before harvest.…”
Section: Methodsmentioning
confidence: 99%
“…A number of WBM site inhibitors have been discovered [ 14 , 19 , 20 , 21 ], but these have yet to progress sufficiently for thorough interrogation in cells or animal models. The discovery of WIN site inhibitors (WINi), in contrast, has been very successful (e.g., [ 1 , 2 , 15 , 16 , 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]), due in large part to the tractability of the WIN site and a deep understanding of structure–activity relationships in this class of agents. Given their prominence, advanced state, and the extent to which they have been profiled in vitro and in vivo, it is likely that WINi will dominate the field in the near future.…”
Section: Strategies To Target Wdr5mentioning
confidence: 99%
“…(2021) demonstrated that the specific WDR5 degrader MS67 effectively reduced WDR5 levels in cells and suppressed tumor growth in patient-derived mouse models ( 30 ). In addition, peptide-mimetic drugs have been employed to target arginine-binding pockets or hydrophobic cavities located on the opposite side ( 31 , 32 ).…”
mentioning
confidence: 99%